Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1515/oere-2015-0026
|View full text |Cite
|
Sign up to set email alerts
|

AlGaN/GaN HEMT’s photoresponse to high intensity THz radiation

Abstract: We report on the photoresponse dependence on the terahertz radiation intensity in ALGaN/GaN HEMTs. We show that the ALGaN/GaN HEMT can be used as a THz detector in CW and in pulsed regime up to radiation intensity of several kW/cm

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…At large intensities of the incident THz radiation, the response has been observed to saturate in the measurements [14]. Different propositions have been made to explain this effect [15], [16], [17]. In this work we explore the reason for the response saturation effect by examining different physical mechanisms in the physics-based simulations using the validated TCAD models [18].…”
Section: Introductionmentioning
confidence: 99%
“…At large intensities of the incident THz radiation, the response has been observed to saturate in the measurements [14]. Different propositions have been made to explain this effect [15], [16], [17]. In this work we explore the reason for the response saturation effect by examining different physical mechanisms in the physics-based simulations using the validated TCAD models [18].…”
Section: Introductionmentioning
confidence: 99%
“…the observed photoresponse is linear in radiation intensity [14]. However, for high excitation levels, Schottky diodes and FETs can be driven into saturation [15][16][17]. Recently, the application of this device regime for fast autocorrelators providing information on the THz pulse duration and pulse structure [1,18] was reported.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, a few different types of antennas or couplers have been realized and examined in FET-based detectors. [17][18][19][20][21][22][23] Recently, Boppel et al found that an FET detector coupled with symmetric antennas is able to detect the intensity gradient and hence allows for direct edge detection. [14] They further pointed out that the asymmetry in the antenna-coupled FETs has to be assured so that the devices can be used as pure power detectors and become insensitive to the intensity gradient.…”
Section: Introductionmentioning
confidence: 99%